A. Bernard Knapp. Seafaring and seafarers in the Bronze Age Eastern Mediterranean. - Wallace, Saro (Journal of Greek Archaeology, 2021)
This well-priced short paperback (176 pages of text) has full references, an index, well-chosen and striking illustrations (the cover showing a Balearic scene) and several useful tables listing Ugaritic, Egyptian, Akkadian and Hittite text references of significance to the topic, as well as 5 maps, on which the lettering is somewhat too small for easy use. It will serve an informed public or student audience well as an expert guide to the known facts about how shipping and trade operated in the Bronze Age east Mediterranean, especially the Late Bronze Age (64 pages against 15 on the Early BA and 22 on the Middle BA).